Field Investigation on Anthropogenic Impacted Lowland Riparian Zones - D.Y.S., Mah; Kelvin, K.K, Kuok (Scientific Research, 2013)
A functioning riparian zone is very beneficial to the environment. However, most of the riparian zones have been dis- turbed by man-made implications these days. Public awareness about the issues of environmental conservation includ- ing riparian zones is needed by providing information on critical areas. Therefore, a novel framework is presented here to reveal how well a riparian zone adopts to changes. This paper highlights the field investigation of an altered riparian system along Maong River in Kuching, Sarawak. Investigation of the general riparian health is followed by the studies of its contributing attributes—vegetation cover, human activities and groundwater level, have been carried out. The methods are practicable in harnessing understanding and knowledge of riparian conditions. For a disturbed riparian zone, the findings indicate that 50% - 60% of the study areas are categorized as healthy or functioning riparian systems, at the same time, correlate the influences of the three afore-mentioned attributes.